Redefining Borders between Communities and the Classroom: How Community-based Social Activists can Transform Social Work Education - Lori Chambers; Sheila Cranmer-Byng; May Friedman; Meaghan Ross; Warimu Njoroge; Dawn Onishenko; Camisha Sibyls; Kristin Smith; Andrea Westbrook (Engaged Scholar Journal, 2016)
In the context of service restructuring that has gravely impacted quality of life for social workers and the people with whom they work, this paper considers the ways that social work education can better support social justice-based social work practices in urban communities in Canada. The paper’s authors attended a fall 2013 Ryerson University forum that brought together critical social work educators and community-based activist social workers struggling to bring social justice-based practices to their work within restructured social services. Examples of social service restructuring include cuts to services, labour intensification, and increased managerialism, processes known as neoliberalism that have shifted discourses away from quality of life toward a focus on economic markers and efficiencies. The purpose of our forum was to explore ways in which social work curricula and pedagogical practices can be challenged and redefined in order to better support those efforts by social workers to resist such processes and to enhance social worker and client quality of life. Our paper presents the findings of this forum, including the presentation and discussion of a series of recommendations to reconfigure social work education so that it is more congruent with the needs of social justice-based practice in social work.